2022
DOI: 10.1039/d2ce01080a
|View full text |Cite
|
Sign up to set email alerts
|

Development and assessment of an improved powder-diffraction-based method for molecular crystal structure similarity

Abstract: Identifying whether two experimental crystal structures determined under different experimental conditions correspond to the same polymorph is a challenging problem in crystallography, and its solution has practical (and even legal)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Similarity indices based on powder diffraction pattern comparisons, particularly de Gelder et al's index, 26 are among the most popular in the literature for the purpose of structural comparison. 19,21,[40][41][42] Indices based on realspace distances, 20,[45][46][47][48][49][50][51][52][53] in particular the popular COM-PACK method, 52 are also widely used, despite the limitations of COMPACK regarding its behavior with respect to variations in the algorithm tolerances. 41 Powderbased indices have as downside that they do not fulfill the mathematical requirements of a metric, 50,51 because two different crystals can share the exact same diffraction pattern.…”
Section: Gaussian Powder-based Similarity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarity indices based on powder diffraction pattern comparisons, particularly de Gelder et al's index, 26 are among the most popular in the literature for the purpose of structural comparison. 19,21,[40][41][42] Indices based on realspace distances, 20,[45][46][47][48][49][50][51][52][53] in particular the popular COM-PACK method, 52 are also widely used, despite the limitations of COMPACK regarding its behavior with respect to variations in the algorithm tolerances. 41 Powderbased indices have as downside that they do not fulfill the mathematical requirements of a metric, 50,51 because two different crystals can share the exact same diffraction pattern.…”
Section: Gaussian Powder-based Similarity Indexmentioning
confidence: 99%
“…In a previous work, we proposed a variable-cell powderbased index built on de Gelder et al's index 26 to compare crystal structures allowing for slight lattice deformations (VC-PWDF). 41 VC-PWDF introduced the idea of a similarity index that considers two structures as exactly equal if there exists an affine transformation (translation, rotation, and anisotropic scaling) that brings both lattices and motifs into exact coincidence. VC-PWDF works by choosing the reduced (Niggli) basis of one of the structures as "target" and then exhaustively exploring all possible bases for the other ("candidate") structure.…”
Section: Introductionmentioning
confidence: 99%
“…It then yields the measure of dissimilarity of the best matching cell with the triangle-weighted cross-correlation function proposed by de Gelder et al 23 The VC-PWDF method has been shown to be as successful as the COMPACK 24 method, which compares crystal structures based on atomic positions. 21,25 Notably, the VC-PWDF method has shown excellent performance for comparison of simulated diffractrograms from in silico structures and those obtained from SC-XRD collected under different experimental conditions. 25 Thus, it forms an ideal basis for a new, high-accuracy method for comparing the experimental powder diffractograms collected during a high-throughput screening to the crystal structures obtained from a CSP study.…”
Section: Introductionmentioning
confidence: 99%
“…Several corrections have been developed to account for the effect of lattice dimension deviations during quantitative crystal structure comparison based on simulated PXRD patterns. These include an isotropic volume correction, 20 the variable-cell powder difference (VC-PWDF) method, 21 and the FIt with DEviating Lattice (FIDEL) method. 22 In this work, we will focus on the VC-PWDF method, which converts input crystal structures to their Niggli reduced cells, then screens possible unit cell bases that may be coincident with the given reference structure, and deforms each candidate unit cell basis to identify the matching cell, if one exists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation